Nuevo estándar de crecimiento intrauterino de la población de Tacna para detección de desnutrición y obesidad al nacer, 2014-2019 - Huanco-Apaza, Diana (2019)
Introduction: Childhood malnutrition and obesity, due to their magnitude and consequences, are public health problems, which in many cases originate from the first periods of intrauterine life. The weight/gestational age relationship is useful to evaluate nutritional risk in the neonatal population. Objective: Build a new intrauterine growth standard for the population of Tacna to detect malnutrition and obesity at birth and compare it with the Lubchenco curve. Material and methods: Cross-sectional study. Neonates from 24 to 42 weeks of gestation born in Tacna from January 2014 to June 2019, from a singleton pregnancy, without congenital malformations, were selected. Mean, standard deviation and birth weight percentiles p10, p50 and p90 were calculated by gestational age, intrauterine growth curve was constructed with percentile data, smoothed with Third Order Polynomial. Weight averages were compared using Student's T. All newborns were classified according to the new curve and Lubchenco, and the proportion of malnourished (<p10) and obese (>p90) was compared using Chi2. The information was obtained from the live birth certificate (CNV) database of the Tacna Health Region. Use Microsoft Excel software. Results: 25,871 live newborns were selected from 26,510. The average weight of the prevalent week 39 was 3563 +406 grams, 10th and 90th percentiles were 2947 and 4087 g. respectively. The Tacna curve was statistically higher than the Lubchenco curve between weeks 36 to 42. 6.8% VS 0.9% of malnourished and 10.5% VS 31.8% of obese were identified between Tacna and Lubchenco curves respectively. (p<0.01). Conclusions: Intrauterine growth standard was obtained for the population of Tacna and it was demonstrated that the Lubchenco curve is not applicable for nutritional evaluation of Tacna newborns because it overestimates obese and underestimates malnourished.